Boosting Tadalafil Bioavailability via Sono-Assisted Nano-Emulsion-Based Oral Jellies: Box-Behnken Optimization and Assessment - Hany S. M. Ali; Sameh A. Ahmed; Abdulmalik A. Alqurshi; Ali M. Alalawi; Ahmed M. Shehata; Yaser M. Alahmadi (MDPI AG, 2022)
Tadalafil (TAD) is a poorly soluble, phosphodiesterase inhibitor used to treat erectile dysfunction. The primary goal of this project was to prepare nano-emulsions using ultrasonic technology to address TAD bioavailability concerns. The Box-Behnken design was employed to find prominent correlations between factors impacting the sono-emulsification process. The emulsifier concentration, amplitude level, and ultrasonication time were the independent factors, whereas the average droplet size (ADS) and polydispersity index (PDI) were designated as the response variables. TAD-loaded nano-emulsions (93-289 nm) were generated and the emulsifier concentration showed a crucial role in directing emulsion droplet size. The model desirability function was utilized to optimize a nano-emulsion with a small ADS (99.67 ± 7.55 nm) and PDI (0.45 ± 0.04) by adjusting the emulsifiers concentration, amplitude level, and ultrasonication time at 9.85%, 33%, 49 s, respectively. The optimized nano-emulsions did not demonstrate any precipitation or phase separation after stability stress tests. TAD jellies were formulated based on the optimized nano-emulsion and subjected to in vitro evaluation for physical characteristics; TAD content, pH, spreadability, viscosity, syneresis, and taste-masking ability. An optimized nano-emulsion-based jelly (NEJ) formulation showed more than 96% drug dissolution in 30 min relative to 14% for the unprocessed TAD. In vivo assessment of NEJ in experimental rats demonstrated a significant enhancement (p < 0.05) of TAD bioavailability with an AUC0-24h of 2045 ± 70.2 vs. 259.9 ± 17.7 ng·h·mL−1 for the unprocessed TAD. Storage stability results revealed that NEJ remained stable with unremarkable changes in properties for 3 months. Overall, NEJ can be regarded as a successful therapeutic option for TAD administration with immediate-release properties and improved bioavailability.